Complex antibacterial and minimally invasive surgical treatment of children with ventriculitis - A. S. Pozhivil; A. Yu. Shcherbuk; A. P. Lyapin; Yu. A. Shcherbuk (Журнал инфектологии, 2019)
Nowadays infectious diseases of brain, despite the great possibilities of modern medicine, remain an important and still unsolved, problem, in neurosurgery. Among such diseases, ventriculitis takes a specific place due to appearance of a life-threatening condition that requires emergency, intensive and long-term treatment, as well as resistance to therapy, high frequency of generalization of infectious process and. relapsing course.Objective: to evaluate the results of treatment of children with ventriculitis, depending on age, pathogenetic type of ventriculitis and applied approaches in treatment, to develop an optimal management for patients with ventriculitis.Methods. The results of examination and. treatment of all patients with ventriculitis admitted, to “N.F. Filatov Children hospital N5", St. Petersburg, from January 2008 to December 2017 were analyzed. A total of 72 patients with ventriculitis aged, from 1 month, to 17 years were treated, during the study period.Results. All patients with ventriculitis received, combined, systemic antibiotic therapy. The intraventricular route of antibiotic administration, was additionally used, in 81.9% of cases. In most cases, patients underwent external ventricular drainage to relieve acute hydrocephalus. In management of children with shunt infection, complete or partial removal of infected, shunt system, was performed, along with external drainage. In some cases, neuroendoscopic surgery were required, such, as endoscopic examination of the ventricular system, with removing pus and. debris, followed, by external drainage, septostomy, fenestration of cysts, removal of the lateral ventricle foreign body, endoscopic third, ventriculostomy.Conclusions. Presently the main tools in the treatment of children with ventriculitis are antibacterial therapy and. external ventricular drainage. Given the problem, of low ability of antibiotics to penetrate the blood-brain barrier, even those recommended, for use in cerebral infections, it is necessary to consider the issue of addition intravenous antibiotic therapy with intraventricular administration, promptly. In case of ventriculitis appearance the implanted, devices (valve shunting systems, external ventricular drains) shall be removed, early and. completely with further placing a new external ventricular drainage, which is necessary. Neuroendoscopic surgery in treatment of children with ventriculitis can be used, depending on specific causes and objectives, and. can be indispensable in cases of protracted, ventriculitis.